HAZARDOUS MATERIALS TRANSPORTATION WITH FOCUSING ON INTERMODAL TRANSPORTATION: A STATE-OF-THE-ART REVIEW - Fattahi, Zahra; Behnamian, Javad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
Transportation of hazardous materials (hazmat) is one of the most critical issues in transportation planning that involves multiple risks to the physical and social environments. Any improvements in it reduce not only environmental costs but also reduces external transport costs (e.g., reduces the risk of accidents which, in addition to environmental impact, also affects external costs). Besides, multi-modal transportation as a main part of transportation uses multiple modes (e.g., rail, ship, truck, air) to transport freight. If the containers carry hazmat, the government regulates their transportation due to the associated risks. Many researchers have studied the risk assessment of hazmat transportation to find ways for reducing hazardous material transportation risks. In this regard, the intermodal models and unimodal problems for hazmat transportation were studied by some researchers. In this study, after pointing out the importance of hazmat intermodal transportation and risks, the research related to hazmat intermodal transportation, including routing and scheduling, intermodal transportation, and location-routing problems. Then the reviewed literature is quantified and measured. Finally, the paper concludes by presenting some problems receiving less attention than the others and proposes several research opportunities in the field.